Harry Potter and the deathly hallows - Rowling, J.K. (New York : Scholastic Inc., 2007)
Burdened with the dark, dangerous, and seemingly impossible task of locating and destroying Voldemort's remaining Horcruxes, Harry, feeling alone and uncertain about his future, struggles to find the inner strength he needs to follow the path set out before him.
One. The dark lord ascending -- Two. In memoriam -- Three. The Dursleys departing -- Four. The seven potters -- Five. Fallen warriors -- Six. The ghoul in pajamas -- Seven. The will of Albus Dumbledore -- Eight. The wedding -- Nine. A place to hide -- Ten. Kreacher's tale -- Eleven. The bribe -- Twelve. Magic is might -- Thirteen. The muggle born registration commission -- Fourteen. The thief -- Fifteen. The goblin's revenge -- Sixteen. Godric's hollow -- Seventeen. Bathilda's secret -- Eighteen. The life and lies of Albus Dumbledore -- Nineteen. The silver doe -- Twenty. Xenophilius Lovegood -- Twenty-One. The tale of the three brothers -- Twenty-Two. The deathly hallows -- Twenty-Three. Malfoy Manor -- Twenty-Four. The wandmaker -- Twenty-Five. Shell Cottage -- Twenty-Six. Gringotts -- Twenty-Seven. The final hiding place -- Twenty-Eight. The missing mirror -- Twenty-Nine. The lost diadem -- Thirty. The sacking of Severus Snape -- Thirty-One. The battle of Hogwarts -- Thirty-Two. The Elder wand -- Thirty-Three. The prince's tale -- Thirty-Four. The forest again -- Thirty-Five. King's cross -- Thirty-Six. The flaw in the plan -- Epilogue.
Keywords: MAGIC -- JUVENILE FICTION